Meeting Standards through Integrated Curriculum: Point of View by Sussan M. Drake and Rebecca C. Bruns - Taseman; Wilujeng Asih Purwani; Safaruddin; Nasrul Fuad Erfansyah; Ratna Pangastuti; Abdul Malik Dachlan; Nukh Khozain (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
Through an integrated curriculum, it is expected that the fulfillment of a maximum standard of learning for students' problems while learning, the integrated curriculum will determine the content, processes, materials, and learning materials that teachers do to students in the classroom. Students who have problems are expected to be able to overcome the problem both those who lack achievement and are left behind, the evaluation carried out is also expected to be able to measure the ability of students to improve learning that has been done, besides it can be compared between one school to another with an evaluation. So we need a standard-based approach and an integrated curriculum, the second offers several strategies in developing an integrated curriculum that has been proven in its implementation, thirdly to validate an integrated curriculum by offering examples of integrated curricula that have proven to be successful.